Phospholipase C and myosin light chain kinase inhibition define a common step in actin regulation during cytokinesis. - Wong, R.; Fabian, L.; Forer, A.; Brill, J.A. (BMC Cell Biology, 2007)
Phosphatidylinositol 4,5-bisphosphate (PIP2) is required for successful completion of cytokinesis. In addition, both PIP2 and phosphoinositide-specific phospholipase C (PLC) have been localized to the cleavage furrow of dividing mammalian cells. PLC hydrolyzes PIP2 to yield diacylglycerol (DAG) and inositol trisphosphate (IP3), which in turn induces calcium (Ca2+) release from the ER. Several studies suggest PIP2 must be hydrolyzed continuously for continued cleavage furrow ingression. The majority of these studies employ the N-substituted maleimide U73122 as an inhibitor of PLC. However, the specificity of U73122 is unclear, as its active group closely resembles the non-specific alkylating agent N-ethylmaleimide (NEM). In addition, the pathway by which PIP2 regulates cytokinesis remains to be elucidated.Here we compared the effects of U73122 and the structurally unrelated PLC inhibitor ET-18-OCH3 (edelfosine) on cytokinesis in crane-fly and Drosophila spermatocytes. Our data show that the effects of U73122 are indeed via PLC because U73122 and ET-18-OCH3 produced similar effects on cell morphology and actin cytoskeleton organization that were distinct from those caused by NEM. Furthermore, treatment with the myosin light chain kinase (MLCK) inhibitor ML-7 caused cleavage furrow regression and loss of both F-actin and phosphorylated myosin regulatory light chain from the contractile ring in a manner similar to treatment with U73122 and ET-18-OCH3.We have used multiple inhibitors to examine the roles of PLC and MLCK, a predicted downstream target of PLC regulation, in cytokinesis. Our results are consistent with a model in which PIP2 hydrolysis acts via Ca2+ to activate myosin via MLCK and thereby control actin dynamics during constriction of the contractile ring.